The Impact of Multiculturalism on Public Education, 50 Years Later : A Home for All? - Bilash, Olenka S. (Educational Research E-Books Online, Collection 2024., 2025)
This volume grew out of a symposium held at the University of Alberta in March 2021 in commemoration of the 50th anniversary of official multiculturalism in Canada. Scholars gathered online during the Covid-19 pandemic to take stock and reflect on the extent and ways multiculturalism legislation and evolving policy has impacted education. Scholars used varied and contrasting approaches to educational theory to think about multiculturalism and its impacts, including terror management theory, the riddle scale, art theory and pentimenti, transitional justice, intraminority and interminority relations, the null curriculum, and ideas of cultural humility, hope, and cultural comfort, among others.